Unprecedented in Vitro Antitubercular Activitiy of Manganese(II) Complexes Containing 1,10-Phenanthroline and Dicarboxylate Ligands: Increased Activity, Superior Selectivity, and Lower Toxicity in Comparison to Their Copper(II) Analogs - McCarron, Pauraic; McCann, Malachy; Devereux, Michael; Kavanagh, Kevin; Skerry, Ciaran; Karakousis, Petros C.; Aor, Ana C.; Mello, Thais P.; Santos, Andre L. S.; Campos, Debora L. [UNESP]; Pavan, Fernando R. [UNESP] (Frontiers Media Sa, 2018)
Mycobacterium tuberculosis is the etiologic agent of tuberculosis. The demand for new chemotherapeutics with unique mechanisms of action to treat (multi)resistant strains is an urgent need. The objective of this work was to test the effect of manganese(II) and copper(II) phenanthroline/dicarboxylate complexes against M. tuberculosis. The water-soluble Mn(II) complexes, [Mn-2(oda)(phen)(4)(H2O)(2)][Mn-2(oda)(phen)(4)(oda)(2)]center dot 4H(2)O (1) and {[Mn(3,6,9-tdda)(phen)2]center dot 3H(2)O center dot EtOH}n (3) (odaH(2) = octanedioic acid, phen = 1,10-phenanthroline, tddaH(2) = 3,6,9-trioxaundecanedioic acid), and water-insoluble complexes, [Mn(ph)(phen)(H2O)(2)] (5), [Mn(ph)(phen)(2)(H2O)]center dot 4H(2)O (6), [Mn-2(isoph)(2)(phen)(3)]center dot 4H(2)O (7), {[Mn(phen)(2)(H2O)(2)]}(2)(isoph)(2)(phen)center dot 12H(2)O (8) and [Mn(tereph)(phen)(2)]center dot 5H(2)O (9) (phH(2) = phthalic acid, isophH(2) = isophthalic acid, terephH(2) = terephthalic acid), robustly inhibited the viability of M. tuberculosis strains, H37Rv and CDC1551. The water-soluble Cu(II) analog of (1), [Cu-2(oda)(phen)(4)](ClO4)(2)center dot 2.76H(2)O center dot EtOH (2), was significantly less effective against both strains. Whilst (3) retarded H37Rv growth much better than its soluble Cu(II) equivalent, {[Cu(3,6,9-tdda)(phen)(2)]center dot 3H(2)O center dot EtOH}n (4), both were equally efficient against CDC1551. VERO and A549 mammalian cells were highly tolerant to the Mn(II) complexes, culminating in high selectivity index (SI) values. Significantly, in vivo studies using Galleria mellonella larvae indicated that the metal complexes were minimally toxic to the larvae. The Mn(II) complexes presented low MICs and high SI values (up to 1347), indicating their auspicious potential as novel antitubercular lead agents.
Keywords: Mycobacterium tuberculosis; manganese(II); 1, 10-phenanthroline; metal-based complex; antimicrobial agent; Galleria mellonella